2008
DOI: 10.3920/wmj2008.1040
|View full text |Cite
|
Sign up to set email alerts
|

Patulin biodegradation using Pichia ohmeri and Saccharomyces cerevisiae

Abstract: The effectiveness of Pichia ohmeri and Saccharomyces cerevisiae in the biodegradation of patulin was evaluated in vitro. Patulin is a toxin produced by Penicillium expansum, the predominant fungal contaminant in post-harvest apple. The biodegradation experiment was carried out in culture medium (Yeast Medium broth, YM) and commercial apple juice. These substrates were artificially contaminated with patulin previously produced by P. expansum strain 2 in malt extract broth and purified over a silica gel column. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…In vitro tests indicated that P. caribbica degraded the mycotoxin directly . Several other yeast species including M. pulcherrima , P. ohmeri , R. kratochvilovae , S. cerevisiae , and Sporobolomyces roseus have also been investigated for their patulin‐degrading capabilities . A R. kratochvilovae (a basidiomycote yeast) strain was able to convert patulin to less toxic desoxypatulinic acid (DPA), representing a novel biodegradation pathway and detoxification process .…”
Section: Applications Of Yeastsmentioning
confidence: 99%
“…In vitro tests indicated that P. caribbica degraded the mycotoxin directly . Several other yeast species including M. pulcherrima , P. ohmeri , R. kratochvilovae , S. cerevisiae , and Sporobolomyces roseus have also been investigated for their patulin‐degrading capabilities . A R. kratochvilovae (a basidiomycote yeast) strain was able to convert patulin to less toxic desoxypatulinic acid (DPA), representing a novel biodegradation pathway and detoxification process .…”
Section: Applications Of Yeastsmentioning
confidence: 99%
“…In view of this, many researches have shown that some antagonist yeasts could directly inhibit the production of patulin. Through almost 30 years of research, dozens of yeasts, including Pichia caribbica [21], Rhodotorula glutinis [22], Pichia ohmeri [23], Rhodosporidium kratochvilovae [24], Gluconobacter oxydans [25], and several others have been shown to degrade patulin, and inhibited the growth of P. expansum . Coelho et al [26] reported that patulin concentration of 223 µg was decreased over 83% by P. ohmeri 158 cells when incubated at 25 °C for two days at a humidity >99.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being successful, this method is much better understood compared with other decontamination methods. Approximately 96% of patulin can be removed during yeast fermentation [242]. Stinson et al [243] examined and found that out of eight yeast strains tested six reduced patulin levels to below detectable levels, while all eight strains resulted in a 99% or better decrease in total patulin content.…”
Section: Biological Controlmentioning
confidence: 99%